APPLIED AND RESIDUAL PHOSPHORUS INFLUENCE ON CERTAIN GROWTH PARAMETERS AND YIELD OF RABI MAIZE SUCCEEDING KHARIF PIGEON PEA - S. NARENDER REDDY, J.K. REVANTH NATHAN, G.E.CH. VIDYA SAGAR , P. LAXMI NARAYANA, A. MADHAVI and (The Journal of Research, PJTSAU, 2021)
A field experiment was conducted at College farm, Professor Jayashankar Telangana State Agricultural University, Rajendranagar, Hyderabad during 2016-17 and 2017-18 to know the applied and residual phosphorus influence on certain growth parameters and yield of rabi maize succeeding kharif pigeonpea in split plot with residual treatments of redgram as main and phosphorus levels of maize as subplot treatments. At harvest, maize plant height (202.05 cm and 203.28 cm respectively) was significantly influenced by application of recommended dose of phosphorus (50 kg ha-1) with 10% urea spraying as defoliant in kharif redgram in both the years under study over non application of defoliant (194.99 cm and 195.82 cm respectively). Leaf area index at 60 (4.93 and 5.21) and 90 days (4.45 and 4.57) also showed similar trend as plant height. In 2016-17 and 2017-18, the grain yield was highest in 75 kg P ha-1 + defoliant (7329 kg ha-1 and 7498 kg ha-1) and it was at par with 50 kg P ha-1 + defoliant (6956 kg ha-1 and 7116 kg ha-1) and these two treatments are significantly superior over others. The stover yield showed similar trend as grain yield.